The Effect of Foot Spa Therapy on Anxiety Reduction Among Hypertensive Patients in the Basic Geriatric Ward of Dr X - Renny Fransiska Aryanti; Son Haji (Jurnal EduHealth, 2026)
Hypertension is one of the most common chronic diseases among older adults and is often accompanied by anxiety, which can negatively affect blood pressure control and overall quality of life. Anxiety may activate the sympathetic nervous system, leading to increased blood pressure and worsening the patient's condition. Foot spa therapy, which combines warm water foot soaking and gentle foot massage, is a complementary non-pharmacological intervention that promotes relaxation, improves peripheral blood circulation, and reduces anxiety. Therefore, comprehensive nursing care incorporating foot spa therapy is needed to support anxiety management in patients with hypertension. This case study aimed to describe the application of foot spa therapy in reducing anxiety among hypertensive patients in the Basic Geriatric Ward of Dr. X, using the nursing process, including assessment, nursing diagnosis, intervention planning, implementation, and evaluation. The study employed a case study design involving two older adult patients with hypertension who experienced anxiety. The assessment identified anxiety related to changes in health status, characterized by excessive worry, restlessness, and sleep disturbances. Nursing interventions included anxiety reduction, therapeutic communication, health education, relaxation techniques, and foot spa therapy administered for two consecutive days. The evaluation showed a significant reduction in anxiety levels. The Geriatric Anxiety Inventory (GAI) score decreased from 13 to 0 in the first patient and from 12 to 0 in the second patient. Blood pressure also improved, decreasing from 155/100 mmHg to 130/90 mmHg in the first patient and from 175/105 mmHg to 130/98 mmHg in the second patient. Subjectively, both patients reported feeling calmer, more comfortable, and less worried about their health condition. Objectively, they appeared more relaxed and cooperative during nursing care. In conclusion, the application of foot spa therapy as part of comprehensive nursing care effectively reduced anxiety and contributed to improved blood pressure among hypertensive patients. Foot spa therapy may be considered a safe, simple, and effective complementary nursing intervention for managing anxiety in patients with hypertension.